Response of Bacillus cereus on Zea mays under different doses of zinc sulphate - Shahzad, Asim (Array, 2021)
Anthropogenic activities have added a large amount of heavy metals to the environment. Heavy metal contaminants affect the physiological and biological properties of soil and plant health. Zinc (Zn) is an essential micronutrient and it promotes plant growth and development but a higher concentration of the metal causes reduction in plant growth. The present study was aimed to evaluate the response of Bacillus cereus on maize plants at different concentrations of ZnSO4 (20, 40 and 60 mg kg–1) amended in the soil under pot experiment conditions. The experiment was conducted by using complete randomized design (CRD) with three replications. Higher doses of ZnSO4 inhibited maize growth and nutrient uptake. However, inoculation of maize seeds with Bacillus cereus at 20 mg kg–1 concentration of ZnSO4 increased seed germination about 39% and plant height by 15%. Moreover, 17% increase in leaf length and a 7% increase in leaf number were observed as compared to control at 20 mg kg–1 concentrations of ZnSO4. Reductions in all growth parameters were observed with 60 mg kg–1 concentration of ZnSO4. The Zn uptake was 75% higher in treatment T8 (uninoculated seeds with 60 mg kg–1 concentration of ZnSO4) as compared to treatments which were inoculated and grown under different zinc concentrations. The results suggest that Bacillus cereus has good potential to remediate Zn from soil as well as to reduce the phyto-availibility and phytotoxicity of zinc.